Unlocking Impact: Transforming Research Visibility With Dissemination Strategies - Charalambides, Alexandros; Grigoriou, Stavri; Wang, I. Kim (My University, 2025)
The European Union has funded €193.3 billion to support innovation research since 1984. Although funding programs are pivotal in maintaining European competitiveness in innovation, their achievements remain little known outside of academic circles. To address this, the European Commission mandates the inclusion of dissemination activities in its funded projects, which can account for fifteen percent of the project's total budget. Still, our survey reveals low public awareness of these funding programs. This paper addresses a longstanding challenge that vexes funding agencies, grant administrators, and innovation managers: how to effectively disseminate the achievements of publicly funded research to the public. We propose a model that addresses all audience types and also ensures broader public engagement. Empirical evidence suggests that effective dissemination for a wider public reach is best achieved through short, human-interest video content shared on public platforms and social media to boost visibility and engagement. Dissemination plans should be repeatable and executed more frequently as the audience size increases.
Keywords: Technological innovation; Artificial intelligence; Social networking; Data mining